Antibacterial Effects of Fluoride in Streptococcus mutans Growth in Vitro - Yura Pradiptama; Marijam Purwanta; Harianto Notopuro (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: Streptococcus mutans is a gram-positive coccus commonly found in the human oral cavity and is a pathogen of dental caries. S. mutans known to form biofilm in infective endocarditis heart-valve. Fluoride usage known to reduce the risk of dental caries. This study aims to analyze how usage of fluoride in inhibiting S. mutans growth.Methods: This study was an experimental study. Antibacterial activity test was performed to evaluate the minimum inhibitory concentration (MIC) using dilution method of sodium fluoride. The minimum bactericidal concentration (MBC) was determined by culturing from the previous dilution test into Chocolate Agar Plate.Results: MIC for sodium fluoride is 4,8 mg/ml and the MBC for sodium fluoride to S. mutans is 4,8 mg/ml. We found S. mutans growth in higher concentration than 19,2 mg/ml. Conclusion: S. mutans was inhibited in dilution test. Growth of the bacteria in higher concentration of sodium fluoride is explained with quasi-irreversible inhibtior effects of fluorida.